Effects of different rapid cooling temperatures and annealing on functional properties of starch straws after thermoplastic extrusion. (1st April 2023) - Wang, Kun; Zou, Feixue; Tao, Haiteng; Gao, Wei; Guo, Li; Cui, Bo; Yuan, Chao; Liu, Pengfei; Lu, Lu; Wu, Zhengzong
Abstract: To improve the performance of starch straws in rapidly cooling and annealing procedure of thermoplastic extrusion, control straw was prepared through slowly cooling at 25 °C, and starch straw was prepared through regulating different rapid cooling temperatures including 20 °C, 5 °C, −10 °C and −20 °C. The results indicated that control straw exhibited a homogeneous state, while starch straws treated by rapid cooling displayed like a wash-board structure. Compared to control straw, the ratio of the absorption peak intensity of 1047 and 1022 cm −1 increased from 1.050 to 1.455 as cooling temperatures decreased from 25 °C to −20 °C, indicating short-range order of the double helix structure significantly enhanced. The relative crystallinities of starch straws increased from 12.01 % to 16.58 %. The maximum bending force value (60.92 N) of starch straws cooled at −20 °C was significantly higher than that (46.14 N) of control straw. Conversely, the modulus of elasticity in bending values (4.21–16.43 N/cm) of rapid cooling-treated straws were significantly lower than that (48.42 N/cm) of control straw. Water absorption of rapid cooling-treated straws were lower than that of control straw, indicating the hydrophobicity property of starch straws significantly improved. Graphical abstract: Unlabelled Image